2011
DOI: 10.1016/j.bbr.2011.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase inhibitors ameliorate cognitive dysfunction induced by amyloid-β peptide in mice

Abstract: The cholinesterase inhibitor, rivastigmine, ameliorates cognitive dysfunction and is approved for the treatment of Alzheimer's disease (AD). Rivastigmine is a dual inhibitor of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE); however, the impact of BuChE inhibition on cognitive dysfunction remains to be determined. We compared the effects of a selective BuChE inhibitor, N1-phenethylnorcymserine (PEC), rivastigmine and donepezil (an AChE-selective inhibitor) on cognitive dysfunction induced by amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…The peptides were then administered by intracerebroventricular (i.c.v.) injection as described previously [37][38][39][40][41].…”
Section: Treatment and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptides were then administered by intracerebroventricular (i.c.v.) injection as described previously [37][38][39][40][41].…”
Section: Treatment and Experimental Designmentioning
confidence: 99%
“…injection of Aβ 1-40 (day 0) [39,41,42]. This method is used to measure of cognitive dysfunction in mouse models of natural aging and AD [43].…”
Section: Novel Object Recognition Testmentioning
confidence: 99%
“…8 Inhibition of BChE also ameliorates Aβ peptide (Aβ 1-40 )-induced memory impairment in mice, which further relates BChE to AD pathogenesis. 14 Pharmacogenomic studies have also revealed the impact of different BChE genotypes on the rate of cognitive decline. Patients with BChE enzyme variants that show reduced activity who were enrolled in a trial of a cholinesterase inhibitor retained attention performance and showed reduced rates of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of drugs increasing activity at nAChRs are also observed in impaired animals. Nicotine and the AChE inhibitor donepezil reverse scopolamine-induced impairment of novel object recognition [134] and both donepezil and the AChE inhibitor rivastigmine reverse impaired novel object recognition in amyloid-beta peptide mice [135]. Further, the a7 nAChR agonist PNU-282987 reverses phencyclidine-induced deficits in novel object recognition [111] and galantamine improves novel object recognition in beta amyloid injected mice and mice impaired by methamphetamine [136,137].…”
Section: Recognition Memorymentioning
confidence: 97%